Form and Function in Baroque Architecture - Botica, Dubravka (Poznańskie Studia Slawistyczne, 2017)
The paper presents relations between form and function in the architecture on few selected examples of theoretical texts. Interrelation of form and function is analyzed on examples of the most important types of baroque architecture – the castle and the church. Baroque castle has a key role in the creation and validation of the power of rulers, enfilade rooms and ceremonial staircase have function of stage on which the ruler displays himself and his power, but also at the same time, reflects strictly hierarchical social system of baroque. In religious architecture, relations between form and function are more regulated. In Instructiones… (1577) of the Council of Trent, the emphasis in the design has been placed on the fulfillment of the functions of post-Tridentine liturgy, from the layout of plan to the new meaning of the triumphal arch. However, the regulations are most clearly expressed at the end of the 18th century, in demand for functionality as the primary goal of a sacred space. Following the adoption of Enlightenment ideas in Central Europe, churches are build according to claim that their design should be “useful and purposeful”, according to the request of Joseph II.